Perkembangan Literasi Informasi Masa Dinasti Abbasiyah - Yahya, Muhammad Nurfauzi; Damang, Widia Fitria Ningsih; Mathar, Muh. Quraisy (Maktabatun: Jurnal Perpustakaan dan Informasi, 2025)
This article aims to explain the Development of Information Literacy during the Abbasid Dynasty. The method used by the researcher is Literature Review. It can be concluded that during the Abbasid Dynasty, literacy and science experienced rapid progress thanks to the policies of the caliphs who supported the dissemination of knowledge and the translation of works from various civilizations. Institutions such as Baitul Hikmah and madrasahs played an important role in education, research, and the development of science, allowing Muslim communities to access broader knowledge. Discussion-based learning methods and library cataloging systems helped disseminate knowledge systematically. In addition, various disciplines, both Islamic and general, developed with the contributions of Muslim scientists in the fields of mathematics, medicine, chemistry, philosophy, and astronomy, strengthening the intellectual foundations of the Islamic world. The translation movement carried out by Abbasid scientists not only enriched the Islamic world but also had a major influence on the development of global science. The continuity of the academic tradition built in this era contributed to the modern education system and intellectual revival in Europe. The value of literacy and the integration of various disciplines from the Abbasid period remain the main principles in the academic world today, encouraging critical thinking, innovation, and more open access to information for the wider community.